A systematic approach to solving the optimization problems of management of technological lines - Shevchenko, Yuliia; Novytskyi, Igor (My University, 2024)
The task of creating a technological line is generally reduced to three stages: 1) development of the design of individual devices of the technological line; 2) selection of the inventory of line devices from the available range (most often by performance) and 3) connecting them into a single structure; operational management of the technological line. Unfortunately, the above are often considered as separate tasks, which does not allow optimization of the technology creation process according to a global criterion .
Keywords: global criterion; technological line; line devices; operational management